Critical factors to green mining construction in China: A two-step fuzzy DEMATEL analysis of state-owned coal mining enterprises. (10th November 2020) - Qi, Rui; Li, Sha; Qu, Lu; Sun, Li; Gong, Chengzhu
Abstract: The efficient deployment of green mining policies is an essential precondition for China to achieve its 2025 green mining construction goal. To identify the critical factors in green mining construction and help policy makers develop more effective policies, this paper conducts an overall investigation on executed green mining policies and proposes an evaluation system of green mining construction. For the sake of clarity, all the related policies has been divided into 5 categories including financial factors, regulatory factors, organizational factors, social factors and technical factors. To disentangle the interrelations between factors and ascertain the critical factors, an improved two-step fuzzy DEMATEL model is adopted for assessment with group knowledge from several long-term and experienced experts in state-owned coal mining enterprises. Results reveal that the regulatory factors and organizational factors, especially the political pressure of local governments and the administrative ranking of enterprise leader, are the critical factors to green mining construction in China, and the social factors are relatively insignificant. It can be concluded that the green mining construction is still politically driven campaign-based governance. Thus, it need priority stipulate the respective benefits and responsibilities, and then run the punitive and incentive policies such as environmental taxes, subsidies, and rewards. Highlights: Summarize and refine the relevant influencing factors of GMC in China. An improved two-step fuzzy DEMATEL method is proposed for factors evaluating. Interrelations among factors are disentangled and the critical factors are ascertained. Regulatory and organizational factors have greater impact on GMC than social factor.